New records of Asteraceae for the Peruvian flora - Beltrán, Hamilton; Museo de Historia Natural, Universidad Nacional Mayor de San Marcos. Av. Arenales 1256, Apartado 14-0434, Lima, PERÚ (2019)
Eighth species of Asteraceae are recorded as new for the Peruvian flora.flora of Peru are reported. Elapahandra lehmannii and Mutisia magnifica were previously known from Ecuador, whereas Achyrocline latifola, Baccharis tridentata and Ericentrodea davidsmithi from Bolivia. Chaptalia piloselloides and Hieracium erianthum are widely distributed in South America and Bellis perennis is a native species of Europe.